New series of avenanthramides in oat seed. Issue 12 (2nd December 2014) - Ishihara, Atsushi; Kojima, Kana; Fujita, Takeshi; Yamamoto, Yuya; Nakajima, Hiromitsu
Abstract: Avenanthramides are characteristic constituents of oat seeds. We analyzed the methanol extract of oat seeds by HPLC and detected three compounds 1, 2, and 3 eluted at retention times similar to avenanthramides. The three compounds were purified by column chromatography and HPLC. Spectroscopic analyses of 1, 2, and 3 suggested that they are amides of 4, 5-dihydroxyanthranilic acid with caffeic, p -coumaric, and ferulic acids, respectively. Their identities were confirmed by comparing spectra and chromatographic behavior with compounds synthesized from 4, 5-dihydroxyanthranilic acid and N -hyrdroxysuccinimide esters of hydroxycinnamic acids. LC-MS/MS analysis with multiple reaction monitoring showed that the amounts of 1, 2, and 3 were 16.5–26.9% of corresponding avenanthamides with 5-hydroxyanthranilic acid. Compounds 1, 2, and 3 showed stronger 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activity than the corresponding avenanthramides with 5-hydroxyanthranilic acid, indicating the involvement of 4, 5-dihydroxyanthranilic acid moiety in the scavenging of DPPH radicals. Graphical abstract: : New series of avenanthramides that contain a 4, 5-dihydroxyanthranilate moiety were identified in oat seeds.